Hydroxyurea therapy modulates sickle cell anemia red blood cell physiology: Impact on RBC deformability, oxidative stress, nitrite levels and nitric oxide synthase signalling pathway - Nader, Elie; Grau, Marijke; Fort, Romain; Collins, Bianca; Cannas, Giovanna; Gauthier, Alexandra; Walpurgis, Katja; Martin, Cyril; Bloch, Wilhelm; Poutrel, Solène; Hot, Arnaud; Renoux, Céline; et al. (Nitric oxide, 2018)
Hydroxyurea (HU) has been suggested to act as a nitric oxide (NO) donor in sickle cell anemia (SCA). However, little is known about the HU NO-related effects on red blood cell (RBC) physiology and NO signalling pathway. Thirty-four patients with SCA (22 under HU treatment (HU+) and 12 without (HU-)) and 17 healthy subjects (AA) were included. RBC nitrite content, deformability and reactive oxygen species (ROS) levels were measured. RBC NO-synthase (RBC-NOS) signalling pathway was assessed by the measurement of RBC-NOS serine1177 and RBC-AKT serine473 phosphorylation. We also investigated the in vitro effects of Sodium Nitroprusside (SNP), a NO donor, on the same parameters in SCA RBC. RBC nitrite content was higher in HU+ than in HU- and AA. RBC deformability was decreased in SCA patients compared to AA but the decrease was more pronounced in HU-. RBC ROS level was increased in SCA compared to AA but the level was higher in HU- than in HU+. RBC-NOS serine1177 and RBC-AKT serine473 phosphorylation were decreased in HU+ compared to HU- and AA. SCA RBC treated with SNP showed increased deformability, reduced ROS content and a decrease in AKT and RBC-NOS phosphorylation. Our study suggests that HU, through its effects on foetal hemoglobin and possibly on NO delivery, would modulate RBC NO signalling pathway, RBC rheology and oxidative stress. •Hydroxyurea (HU) increases red blood cell (RBC) deformability in sickle cell patients.•RBC NO content is increased and RBC-NOS activation decreased in HU-treated patients.•Reactive oxygen species level is decreased in HU-treated patients.•Sodium nitroprusside modulates RBC deformability and RBC-NOS activation.